Curve-centered plaques raise the risk of peri-operative neurological and cardiovascular complications during angioplasty and stenting for severe carotid stenosis - Kang, Chul-Hoo; Rhim, Jong-Kook; Kim, Hong Jun; Choi, Jay Chol; Kim, Joong-Goo (Frontiers in Neurology, 2024)
Introduction Carotid artery stenting is an alternative interventional treatment to carotid endarterectomy. However, preprocedural considerations and anatomical risk factor analyses for carotid artery stenting are currently insufficient. Therefore, we investigated the high-risk anatomical appearance of carotid artery stenting from the neurointerventionist perspective to predict periprocedural complications. Materials and methods We retrospectively reviewed patients with carotid stenosis who underwent carotid artery stenting at a comprehensive stroke center between January 2012 and December 2021. We compared the demographic characteristics, medical history, and anatomical appearance of the stenotic segment in patients with and without complications. Results We analyzed a total of 148 patients (64 women [43.2%]; median age, 73.0 [interquartile range, 65.5–79.0]). Complications occurred in 39 of the 148 patients, primarily minor and transient. Of baseline or procedural characteristics, a high initial National Institutes of Health Stroke Scale score (p = 0.04), symptomatic stenosis (p = 0.01), and curve-centered plaque of the proximal ICA (p = 0.01) were significantly associated with carotid artery stenting complications in unadjusted analysis. Curve-centered plaque remained an independent risk factor for carotid artery stenting complications after adjustment (odds ratio 2.23[1.02–4.88], p = 0.04). Conclusion High-risk vascular anatomical features, such as curve-centered plaque, are associated with a high frequency of periprocedural complications of carotid artery stenting. Tailored patient selection for carotid stenosis is crucial to prevent complications. Patients with curve-centered plaque should consider alternative treatment options such as carotid endarterectomy to achieve optimal clinical results.